CO2 solubility in aqueous potassium lysinate solutions at absorber conditions. (August 2017) - Zhao, Yue; Shen, Shufeng; Bian, Yangyang; Yang, Ya-nan; Ghosh, Ujjal
Highlights: The solubility of CO2 in aqueous LysK systems was measured. Two models were used to correlate the solubility data. The heat of absorption for LysK was estimated as about 55–70 kJ/mol. Abstract: In this work, CO2 solubility in aqueous potassium lysinate solutions has been measured for the concentrations of (1.25–3.28) mol·kg −1 and at temperatures of (313–343) K. The vapour-liquid equilibrium data were correlated using a Soft model and a semi-empirical (SE) model. The proposed models can match well with the experimental data with AAD within 20%. The heat of absorption for LysK was estimated as about (55–70) kJ·mol −1 CO2 absorbed from the solubility data. The lower heat of absorption, compared with that of 30 mass% MEA, will be beneficial for the reduction of regeneration energy.